All fall down debt, deregulation and financial crises - D'Arista, Jane W. (Cheltenham Edward Elgar Publishing, 2018)
All Fall Down traces the ways in which changes in financial structure and regulation eroded monetary control and led to historically high levels of debt relative to GDP in both developed and emerging economies. Rising stocks of debt drove the global financial system into crisis in 2008 when households, businesses, financial institutions and the public sector in some countries strained to generate sufficient income for debt service. The stagnation and fall in asset prices that followed began the process of unwinding that led to a run on the financial sector by the financial sector.
Includes bibliographical references (pages 223-232) and index.
Keywords: Finance--United States